The young handball player - Achenbach, L. (Handball Sports Medicine, 2018)
Engaging in team handball at a young age has important physical health benefits but also involves risk of injury. Youth handball players may be particularly vulnerable to injury due to growth-related factors such as the growth spurt, susceptibility of the growth plate, and differing physiological response after training and match load. The more frequent and intensive training and competition of young elite handball players may create conditions under which these potential risks can more readily exert their influence. The purpose of this chapter is to provide a current overview of risks related to physical and psychological injury that may be encountered by youth handball players, especially in the elite youth setting.